Structure–activity relationship of indoloquinoline analogs anti-MRSA. Issue 23 (1st December 2015) - Zhao, Min; Kamada, Tomonori; Takeuchi, Aya; Nishioka, Hiromi; Kuroda, Teruo; Takeuchi, Yasuo
Graphical abstract: Abstract: Indolo[3, 2- b ]quinoline analogs (3a –3s ), 4-(acridin-9-ylamino) phenol hydrochloride (4 ), benzofuro[3, 2- b ]quinoline (3t ), indeno[1, 2- b ]quinolines (3u and3v ) have been synthesized. Those compounds were found to exhibit anti-bacterial activity towards Methicillin-resistant Staphylococcus aureus (anti-MRSA activity). Structure–activity relationship studies were conducted that indoloquinoline ring, benzofuroquinoline ring and 4-aminophenol group are essential structure for anti-MRSA activity.